Pascu-Type Analytic Functions by Using Mittag-Leffler Functions in Janowski Domain. (12th August 2021) - Mashwan, Wali Khan; Ahmad, Bakhtiar; Khan, Muhammad Ghaffar; Mustafa, Saima; Arjika, Sama; Khan, Bilal
Abstract : Keeping in view the various important applications of Mittag-Leffer functions in the fields of applied sciences, we introduce Pascu-type analytic functions utilizing the concept of Mittag-Leffler functions in the region of Janowski domain. Moreover, we investigate some useful properties of these functions such as sufficiency criteria, distortion and growth bounds, convex combination, radius of starlikeness, and some partial sum results.